Multimedia transmission over interworking of Bluetooth WPAN and IEEE 802.11g WLAN networks - Ahmad, Mohd. Ridzuan; Abd. Rahman, Tharek (2005)
Multimedia services, which are the topic of this research, audio-video conferencing and video streaming, have gained much popularity in the last years. This has been enabled by the high increase of computing power in home personal computers (PCs), which allows usage of very efficient video compression technologies. Motion picture experts group (MPEG) 1, 2 and 4, and Real video can reduce the size of video clips by a factor of 200 - 1000 thus making it possible to put such transmission into regular computer networks, including wireless. This research focuses on testing the possibilities of multimedia transfer given by two of the most promising wireless technologies, which are Bluetooth and wireless local area network (WLAN) located in the Wireless Communication Centre (WCC) building. Speeds up to 721 kilobit per second (kbps) allow not only transmission of the Web pages, e-mail, and chat but also conferencing with video and audio or streaming of live shows like sports matches or movies. This research discusses possibilities of audio and video transmission over Bluetooth wireless personal area network (WPAN) and IEEE 802.11g WLAN links: which scenarios are possible, what kind of software may be used and where is the actual limit of the Bluetooth speed, i.e. how much of the bandwidth is actually available for the transmission. The reliability of Bluetooth WPAN is then estimated under the stated conditions and scenarios.